Pengaruh Motivasi terhadap Minat Mahasiswa Akuntansi untuk Mengikuti Pendidikan Profesi Akuntansi (PPAk) - Andoko, Candra Yuli (Akmenika: Jurnal Akuntansi dan Manajemen, 2015)
This study aim to reveal the influence of quality motivation, economic motivation and achievement motivation towards Accounting students’ interest in taking Accounting profession education. This study was conducted in Yogyakarta in academic year 2013/2014. This study is a quantitative using Cluster Sampling technique or grouping sample taking. As the population was Accounting students in Yogyakarta. The total number of sample was 140 form 3 private universities with B accreditation. The analysis technique used was bifilar regression analysis with 0,05 of the significance level. The result of the study showed that wholly, motivation such quality motivation, career motivation, economic motivation and achievement motivation had influence over the interest of Accounting student to take the PPAk with 0,000 of the significance value. However, partially the quality motivation and achievement motivation did not influence the interest of students to take the PPAk with 0,367 and 0,210 of significance value each. Variables which were significantly influential towards students’ interest to take the PPAk were career motivation with 0,02 of significance value and economic motivation with 0,04 of significance value.